Screening and comparative study of in vitro antioxidant and antimicrobial activities of ethanolic extracts of selected Vietnamese plants. Issue 1 (1st January 2020) - Le Anh Dao, Nguyen; Phu, Tran Minh; Douny, Caroline; Quetin-Leclercq, Joëlle; Hue, Bui Thi Buu; Bach, Le Thi; Quynh Nhu, Truong; Thi Bich Hang, Bui; Thi Thanh Huong, Do; Thanh Phuong, Nguyen; Kestemont, Patrick; Scippo, Marie-Louise
ABSTRACT: This study aimed to screen the in vitro antioxidant and antimicrobial activities of ethanolic extracts from 20 plants and three herbal commercial products empirically used for aquaculture improvement in Vietnam. The results of 2, 2-diphenyl-1-pycrylhydrazyl (DPPH) radical scavenging assays showed that Phyllanthus amarus extract was the strongest antioxidant, followed by four extracts in the subsequent order: Piper betle > Psidium guajava > Euphorbia hirta > Mimosa pudica . These five plant extracts were very active in a DPPH radical scavenging assay with concentrations needed to scavenge half of the DPPH (IC50 ) below 30 µg/mL. Seven plant extracts showed an IC50 ranging from 31.9 to 59.7 µg/mL, while eleven extracts showed an IC50 above 70 µg/mL. A positive association was found between phenolic content (expressed as gallic acid equivalents) and antioxidant activity of the plant extracts. Concerning in vitro antimicrobial activities, P. amarus extract showed the highest activity against two different strains of Aeromonas hydrophila as demonstrated by its low minimal inhibitory concentration (MIC) of 156 and 625 µg/mL, respectively; whereas, P. betle displayed a moderate activity against Edwardsiella ictaluri with a MIC value of 625 µg/mL. Tannins were observed as significant factors contributing to antioxidant and antimicrobial properties of the plant extracts tested.